The beneficial effects of Pumpkin (Cucurbita pepo L.) seed oil for health condition of men. Issue 2 (17th February 2019) - Ramak, Parvin; Mahboubi, Mohaddese
ABSTRACT: Pumpkin seed oil, a dark greenish red oil, extracted from Cucurbita pepo L. oval seeds, is rich in essential highly unsaturated fatty acids with predominant oleic and linoleic acid content, and phytosterols. The aim of this review article was to evaluate the efficacy of pumpkin seed oil in men's health. We used the clinical trials on the efficacy of pumpkin seed oil on different health conditions of men. The clinical trials were focused on the administration of pumpkin seed oil as alternative treatment in Benign Prostatic Hyperplasia (BPH), overactive bladder, and androgenic alopecia. The effects of the oil are related to phytoestrogens and unsaturated fatty acids content. The proposed mechanisms related to these efficacies are due to its inhibitory effects on 5-α-reductase, anti-inflammatory effects or the ability to scavenge free radicals. Also, relaxation effects on bladder sphincter may help the patients with difficulties in urination. Therefore, there is a need for further evaluation of these and other biological effects of pumpkin seed oil in pharmacological and clinical trials. Abbreviations: Benign Prostatic Hyperplasia (BPH), Dihydrotestosterone (DHT), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), overactive bladder system score (OABSS), Aspartate Aminotransferase (AST), Alanine transaminase (ALT), y-glutamyltransferase (GGT), prostate specific antigen (PSA), phosphodiesterase type 5 (PDE-5) Practical applications : The seeds, fruits, and leaves are used ethnobotanically as functional food. The seeds oil are rich in phytosterols (desmosterol, campesterol, stigmasterol, β-sitosterol, spinasterol, D7, 22, 25-stigmastatrienol, D7-stigmastenol, D7, 25-stigmastadienol, and D7-avenasterol), fatty acids, squalene, tocopherols, and other healthy components. The components make it as alternative medicine for management of health in men. It has beneficial effects on Benign Prostatic Hyperplasia, over active bladder, and androgenic alopecia.